Geometric simplification and refinement of 3D graphics in collaborative design - Cai, Yanling (2014)
Two challenging problems that hinder the development of collaborative design are large CAD files and limited Internet bandwidth. 3D streaming technology provides a potential solution to overcome these obstacles. Mesh simplification and progressive refinement of 3D graphics are the key elements of the streaming technology. In this report, we have studied current technologies of mesh simplification and progressive refinement as well as the application of 3D streaming in collaborative design.